2019
DOI: 10.1155/2019/2947170
|View full text |Cite
|
Sign up to set email alerts
|

Antiageing Performance Evaluation of Recycled Engine Oil Bottom Used in Asphalt Rejuvenation

Abstract: To comprehensively evaluate the antiageing performance of recycled engine oil bottom (REOB) used in asphalt rejuvenation, ageing performance studies were carried out on REOB, REOB-rejuvenated asphalt, and REOB-rejuvenated asphalt mixture. The thin film oven test (TFOT) results of REOB and a professional regenerant, RA5, were compared to verify the ageing resistance of REOB as an asphalt regenerant. The quality and viscosity of REOB-rejuvenated asphalt, RA5-rejuvenated asphalt, and base asphalt were measured af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The U.S. Strategic Highway Research Program (SHRP) uses the rutting factors G* and sin δ as rating indexes for the high-temperature performance of asphalt [ 33 , 34 ]. In this study, a continuous high-temperature performance gradation (PG) analysis was conducted for SPMA and SCESPMA with reference to ASTM D 7643-16, and the specific results are shown in Figure 12 .…”
Section: Resultsmentioning
confidence: 99%
“…The U.S. Strategic Highway Research Program (SHRP) uses the rutting factors G* and sin δ as rating indexes for the high-temperature performance of asphalt [ 33 , 34 ]. In this study, a continuous high-temperature performance gradation (PG) analysis was conducted for SPMA and SCESPMA with reference to ASTM D 7643-16, and the specific results are shown in Figure 12 .…”
Section: Resultsmentioning
confidence: 99%
“…e research team detected the existence of WEOB in asphalt by microscopic methods and verified the hypothesis that the early failure of asphalt pavement is related to the existence of WEOB [12]. After that, some researcher studied the influence of WEOB from different sources on the property of asphalt binder and found that WEOB had a negative impact on the high-and low-temperature performance of asphalt [13,14].…”
Section: Introductionmentioning
confidence: 90%
“…However, different researchers hold diametrically opposite views on the promotion effect of WEOB on the property of asphalt binder [4,[14][15][16]. For instance, Qurashi et al [7] evaluated the properties of WEOB-modified bitumens and found that WEOB increases the grade span and reduces the cracking performance of bitumen.…”
Section: Introductionmentioning
confidence: 99%
“…Miaozhang Yu [ 12 ] compared the performance and content of each component of three REOB and regulated regenerants to verify the theoretical feasibility of REOB as a regenerant. Li Jin [ 13 , 14 , 15 , 16 ] et al used REOB as an asphalt regenerant and investigated the high and low temperature performance of REOB rejuvenated asphalt using asphalt conventional performance test, dynamic shear rheology (DSR) test, and asphalt bending creep stiffness (BBR) test, and found that 7% of REOB could achieve complete regeneration of the three major indexes of aged asphalt, but the low temperature performance recovery was insufficient compared to the original sample base asphalt. It is usually challenging to return aged asphalt regeneration to the level of performance of the new base asphalt, while the use of composite modification can be more targeted to improve and optimize the asphalt performance within a controlled range, improving its road performance [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%